Formal Legality of the Status of the Fitrah Zakat Amil Committee of the Mosque in Tanjung Morawa B Village, Tanjung Morawa District According to Zakat Regulations in Indonesia - Iqbal, Muhammad Nur; Herisiswan, Herisiswan; Yamamah, Ansari (Journal of Law, Politic and Humanities, 2025)
Islamic law regulates zakat during the time of the Prophet Muhammad SAW and the Khulafaurrasyidin . Zakat has been managed by amil zakat since the time of the Prophet Muhammad SAW and the Khulafaurrasyidin . One example is when the Prophet Muhammad SAW sent Muadz bin Jabal to Yemen, where he collected zakat from the people while he was governor of the country. The purpose of this study is to determine the understanding of the amil zakat fitrah committee in Tanjung Morawa B Village, Tanjung Morawa District regarding the process of appointing amil zakat. To determine the authority of appointing amil zakat according to Zakat Regulations in Indonesia and to determine the legality of the status of the manager of amil zakat mosques in Tanjung Morawa B Village, Tanjung Morawa District according to Zakat Regulations in Indonesia. The research method used in this discussion is a qualitative research method. The approach used by the author in discussing this research is an empirical or sociological approach . The data collection method used by the author is by means of field observation and reviewing the data sources that the author mentioned, namely primary, secondary, and tertiary. The results of the study show that the process of forming the amil zakat fitrah committee in Tanjung Morawa B Village, Tanjung Morawa District , was carried out at the end of the month of Ramadan by holding a gathering or meeting to determine the amil zakat fitrah committee for that year, and the tradition in Tanjung Morawa B Village, that the amil zakat fitrah committee does not change every year unless someone moves house or has passed away . The formation of the amil zakat fitrah committee for the Mosque in Tanjung Morawa B Village, Tanjung Morawa District can be said to be illegal. Because it does not submit according to procedures according to Law Number 23 of 2011, Government Regulation Number 2014, and BAZNAS Regulation Number 2 of 2016